Effectiveness of Sunscreen in Preventing Skin Problems - Wibawa, Galang Edi; Yuar, Alana Akmal; Rahmawati, Fadila; Maurae, Perlin Nigel Valencia; Hakim, Baiq Sheila Oktalia; Bisa, Muhammad Rizky Yolanda; Paramadinda, Ni Made Ayu Mas Sista; Aulia, Siti Zahroni; Rabbani, Yaskuna Urfi (Jurnal Biologi Tropis, 2025)
Sunlight contains ultraviolet (UV) radiation, which is part of the electromagnetic spectrum. Low awareness of the importance of skin protection, as well as the perception that sunscreen use is incompatible with masculine image, is due to a lack of education. This paper aims to discuss the importance of sunscreen use as a preventive measure in maintaining skin health, especially in areas with high UV exposure such as NTB. The results of a literature study found that ultraviolet light is part of the electromagnetic spectrum originating from the sun. UVA, UVB, and UVC rays are the three types of these rays that may be distinguished by their wavelength. One of the major risk factors for developing skin cancer is exposure to UVA and UVB radiation. Sunscreen is one way to chemically protect the skin from the sun. Active ingredients in sunscreen have the ability to absorb, disperse, and reflect sunlight to provide the best possible protection for the skin. The chemical structure known as aromatic molecules conjugated with carbonyl groups is the mechanism of action of chemical sunscreens. The degree of hyperpigmentation is greatly impacted by proper sunscreen use. In conclusion, the public should be taught about the importance of wearing sunscreen in order to avoid the acute and long-term consequences of excessive UV exposure.